PROSES PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN FAHMUSSALAM AL-AZIZIYAH DALAM TINJAUAN PSIKOLOGI INTUITIF - S, Fahrurrozi; Ichsan, Sayed Muhammad; Kusuma, Al halim (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
Arabic language learning is a central part in shaping the personality of students in understanding and knowing Arabic as a whole and in-depth for future generations, and the current tendency of Arabic language learning focuses on the empirical ratio aspect marked by the use of Western theory as a basis for learning so that spiritual aspects are only taught in the private sphere. Pesantren Fahmussalam provides a new breakthrough in Islamic education by making the teachings of tarekat alawiyah in Arabic language learning, namely the practice of the book Maulid Dhiyau Al-Lami ' by Habib Umar bin Salim bin Hafidz. The method used in this research is qualitative with a literature study approach and interviews as a research base, where researchers make direct observations in observing Arabic language learning at fahmussalam Islamic boarding school. The results of this study indicate that Intuitive Psychology is a new breakthrough in Arabic language education, where participants make spiritual aspects in the learning process not only limited to mere practice, so as to be able to provide and hone their intuitive abilities.